TRENDS OF PHARMACEUTICAL INDUSTRY PROFESIONAL TRAINING IN UKRAINE (20-40’S, 20TH CENTURY) - Slipchuk, Valentina (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the theoretical development of the general statement of the issue of professional training scheme for the pharmaceutical industry and pharmaceutical education and trends of professional training in the pharmaceutical industry in the 20-40’s, 20th century. It reveals that the implementation of the directives of higher authorities have found reflection in the change of work plans, programs, improving the quality of lectures and practical classes, methodical work strengthening, reviewing scientific projects topics, the development of Marxist-Leninist teaching. The main trends of professional training in the pharmaceutical industry were defined, namely: modernization of the Soviet secondary and higher pharmaceutical school under an authoritarian society (reorganization of Ukrainian higher pharmaceutical education by its integration into the unified Soviet state education (unified structure and content of pharmaceutical education, curricula, programs, textbooks, assessment system), ignoring national component (prohibition of Ukrainian language and education on national basis); Russification of the content of professional undergraduate professional training in the pharmaceutical industry; international Soviet education of future professionals of the pharmaceutical industry, the principle of equal access to education, the use of active forms and methods of professional training in the pharmaceutical industry, the communist principle of future professionals education in the pharmaceutical industry through the education content, educational process; restructuring of organizational and pedagogical foundations of professional training in the pharmaceutical industry; updating the content of professional training and evaluation of the pharmaceutical industry, forms and methods in accordance with the educational paradigm, that could meet the state needs.